2016
DOI: 10.1016/j.jiph.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Is the Saudi public aware of Middle East respiratory syndrome?

Abstract: To limit the spread of Middle East respiratory syndrome coronavirus (MERS-CoV) in Saudi Arabia, the Ministry of Health tried to raise public awareness using different public campaigns. We aimed to measure public awareness of MERS in Saudi Arabia. A cross-sectional study was conducted between May and June 2014 using a newly designed Arabic questionnaire that was distributed and completed online. We analyzed the response of 1149 respondents across Saudi Arabia. We found that 97% of the participants were aware of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
80
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 16 publications
35
80
2
Order By: Relevance
“…In addition, highly educated people have the capability to obtain information about the disease from different sources, which cannot be readily accessible to low educated ones. Likewise the same variables were associated with more knowledge in the above mentioned national survey [13].Future interventions should target the youngers and individuals with low educational background.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, highly educated people have the capability to obtain information about the disease from different sources, which cannot be readily accessible to low educated ones. Likewise the same variables were associated with more knowledge in the above mentioned national survey [13].Future interventions should target the youngers and individuals with low educational background.…”
Section: Discussionmentioning
confidence: 55%
“…The same identified gaps in the treatment domain ( no specific treatment for the disease and no vaccine can prevent from the disease ) were reported in electronically conducted national survey [13]. Future educational messages to raise the awareness of the public should focus on these items as it may motivate them to adhere to strictly to the preventive measures and help in the containment of the disease.…”
Section: Discussionmentioning
confidence: 64%
“…This result was in consistent with the previous studies in other parts of Saudi Arabia which indicated that general Saudi population, health care worker as well as medical students showed a high level of awareness in the clinical aspect of the disease. 11,12,18,19 This awareness could be attributed to the awareness campaigns in the hospital and on social media, which were the most common sources of information. As recommended by CDC, Saudi Arabia has led the relevant authorities to initiate educational campaign targeted towards public and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Students, faculty members and non-academic staff were invited to participate in the study. A previous study indicated that about 54% of the Saudi Arabian public had a good knowledge regarding MERS-CoV infection (5). With a margin of error of 5%, level of confidence of 95% and power of study of 80%, the minimum sample size required was calculated to be 606.…”
Section: Populationmentioning
confidence: 99%
“…Available studies are few and are limited by the small number of participants (3), reporting on participants' personal practices rather than the individual's adherence to the current recommendations, and evaluating only minor aspects of public knowledge (3)(4)(5). In general, there is a lack of studies on the awareness and attitude of the Saudi Arabian public towards infectious diseases.…”
Section: Introductionmentioning
confidence: 99%